Teachers' Ability to Develop Social Studies Learning Based on Higher Order Thinking Skills (Hots) for Improving Critical Thinking Skills - Laharja, Sudaryana; Nurfaizan AM, Hilmi; Hermanto, Odang; Oktariza, Sela (SAHUR Journal, 2023)
The fact that many judgments are based on low-level knowledge, understanding, and application abilities is another issue with the current judging methods. As a result, possibilities for memorization and fact extraction and surface knowledge creation are created. Yet assessments for the twenty-first century must take into account advanced abilities. This study, which was carried out in class VIII, employed a quantitative strategy and descriptive techniques. In this study, 34 respondents were chosen from a sample of 334 students, who made up the population. The study's findings provide an account of the efforts put forward. Based on the analysis and discussion of the impact of the teacher's ability to create HOTS-based learning on students' critical thinking abilities that were stated in earlier chapters, it can be concluded that the efforts made by Social Sciences educators at Asshidiqiyah Middle School have been successful.